(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This paper aims to show the experiences of musicalization and choral singing developed with 7 to 12 years old children by UESC Nucleus of Arts (an Art Project from Universidade Estadual de Santa Cruz, at Ilheus, Bahia State). The activities are organized into two different communities next to the University for offering the institution services to the local neighborhood. It becomes an extensive action with the porpuse of offer access to arts, music and culture for those who live around the University.